The time machine eaudiobook - Wells, H.G (Recorded Books Inc., 1996)
The Time Machine is the fascinating oral diary of the Time Traveler-the first man to journey beyond the conventional limits of time. As the first of H.G. Wells' visionary novels, it created the science fiction genre by giving us a tantalizing glimpse at the future. When the Time Traveler crash-lands in the year 802,701, he is surrounded by lush landscapes and a small, gentle people named Eloi. Amazed by their apparent bliss, he wishes to bring their secrets back to his troubled time. As the sun sets, however, all harmony is shattered when the time machine disappears and the fearsome Morlocks stalk the cowering Eloi. Masterfully narrated by Simon Prebble, this astonishing odyssey into the distant future will thrill young and adult listeners alike. H.G. Wells is the author of many timeless and unforgettable science fiction classics, including The Invisible Man, i.The Island of Dr. Moreau and The War of the Worlds.